Ultrafast dynamics of localized light modes. Issue 1 (24th January 2013) - Leipold, David; Silies, Martin; Mascheck, Manfred; Lienau, Christoph; Runge, Erich; Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> Multiple coherent scattering gives rise to a variety of localization phenomena. However, the localization of electromagnetic waves is notoriously hard to observe. Here, hot‐spots found in optical wavefunctions in the visible range in random zinc‐oxide nano‐needle arrays are discussed. In particular, results from 3D and 2D calculations of light localization in random arrays of dielectric cylinders are compared. While 3D calculations with periodic boundary conditions reproduce various aspects of the experimental results very well, open boundary 2D calculations proof the coexistence of propagating and lossy localized modes showing distinct hot‐spots.